Apigenin inhibits C5a-induced proliferation of human nasopharyngeal carcinoma cells through down-regulation of C5aR. Issue 3 (15th May 2018) - Zhang, Yanshu; Cao, Ying; Zhang, Linlin; Feng, Chunyan; Zhou, Guangquan; Wen, Guohua
Abstract : Complement 5a (C5a) is able to induce the proliferation of human nasopharyngeal carcinoma (NPC) cells. Therefore, an effective method or drug that can specifically inhibit C5a-induced proliferation of human NPC cells needs to be developed. Reportedly, Apigenin has antiproliferative effects on a variety of cancer cells. However, the effect of Apigenin on NPC cell proliferation and its underlying mechanism are still unclear. Herein, the present study aimed to evaluate the effect of Apigenin on C5a-induced proliferation of human NPC cells and its possible mechanism through down-regulation of C5aR. We revealed that Apigenin in vitro could not only inhibit proliferation of NPC cells and but also reduce the expression of C5aR and P300/CBP-associated factor (PCAF) as well as the activation of signal transducer and activator of transcription 3 (STAT3) in NPC cells. Furthermore, Apigenin reduced the proliferation of human NPC cells triggered by C5a through negative regulation of C5aR/PCAF/STAT3 axis. These might provide a new insight into the function of Apigenin in cancer treatment, and also provide a potential strategy for treating human NPC through inhibition of C5aR expression on cancer cells.